On the Issue of Studying the Functional Features of the Body of Student-Sportsmen in the Conditions of the Republic of Karakalpakstan (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the issues of studying the functional characteristics of the body of student-sportsmen in the conditions of the Republic of Karakalpakstan. It is noted that the system-forming factor of functional reserves indicates the results of activities that ensure the adaptation of the body of student-sportsmen to various physical loads. It was found that the level of cardiac synchronization characterizes the degree of vegetative balance.